REPRESENTAÇÕES SOCIAIS DE PUÉRPERAS SOBRE VIOLÊNCIA OBSTÉTRICA NO CENÁRIO DO PARTO E NASCIMENTO - LEITÃO, Kassya Rosete Silva (2022)
Obstetric violence has been considered a public health issue for years, and its definition ranges fromdelays in care, refusal of admission to health services, negligent care, refusal to administer analgesics,to physical, verbal and/or psychological abuse, with disrespect for privacy and freedom of choice, performance of coercive or non-consented procedures, detention of women and their babies in health institutions, among others, their existence is still not widespread. The Theory of Social Representations(SRT) are the set of explanations, beliefs and ideas common to a certain group of individuals, resulting from a social interaction, without losing sight, however, of the question of individuality. The TRS is configured as a theory interested in knowing how the formation of knowledge takes place, in addition to the cognitive and social aspects, turning to the construction of popular knowledge. Thus, the guiding question was: “What are the social representations of postpartum women about obstetric violence in the labor and birth scenario?”. This study aimed to analyze the social representations attributed by puerperal women regarding obstetric violence in the context of care in the labor and birth scenario. Study with a qualitative approach based on the theory of Social Representations. Thirty puerperal women attended at the University Hospital Materno Infantil, in São Luís-MA, participated in the study. For data collection, a sociodemographic questionnaire and obstetric data were used to characterize the puerperal women, the free-word association technique (TALP) and an interview script with guiding questions about obstetric violence. The interviews were recorded and later organized by the IRAMUTEQ software. made available the corpus and the grouped words, favoring the identification of the nuclei of meaning. Most women self-declared brown and black, with 1 to 3 children, catholic and housewives, with the current delivery being normal. As for the level of education, most had completed high school. According to the reports, three thematic categories emerged: Understanding Obstetric Violence; Experience of access, Labor and Hospitalization; Associating the experience with obstetric violence. It could be seen that the puerperal women did not understand or did not know the term obstetric violence, in their current experiences of access, labor and hospitalization, they experienced little obstetric violence, which was perceived in previous pregnancies. The social representations of postpartum women about Obstetric Violence is associated with a feeling of insecurity, vulnerability, sensitivity, poor professional behavior, lack of information and autonomy of the puerperal woman, strongly represented by the words: fear, ignorance, pain, disrespect, lack of empathy, abuse and neglect, showing that despite the discussions already held on the subject and the existence of care networks aimed at pregnant and postpartum women, there is still much to develop in order to make this knowledge accessible and in practice the promotion, protection and prevention of this public health problem.